Culturally‐specific Smoking Cessation Outreach in a Rural Community. Issue 1 (30th August 2013) - Butler, Karen M.; Rayens, Mary Kay; Adkins, Sarah; Record, Rachael; Langley, Ronald; Derifield, Stephanie; McGinn, Carolyn; Murray, Deborah; Hahn, Ellen J.
<x xml:space="preserve">Abstract</x> Objective Tobacco use is the leading preventable cause of death, resulting in 443, 000 US deaths per year. Rural adults have higher smoking prevalence and less access to tobacco dependence treatment than their urban counterparts. This study examined exposure to a culturally specific smoking cessation outreach intervention, assessing whether exposure was associated with cessation behaviors. Design and Sample Post‐test only quasi‐experimental study. Targeted adult smokers (N = 251) living in a rural, economically distressed southeastern US county for at least 6 months. Measurements Five outreach elements (brochures/pushcards, posters, print and radio advertisements, quilt made by local artisans) based on themes from focus groups with current and former smokers and paired with brief tobacco cessation counseling, and were delivered over 6 months in 2009–2010. Exposure and cessation behavior indicators were collected via cross‐sectional random‐digit dial survey. The total intervention exposure score was 4.8 (SD = 4.3, range 0–19). Results Intervention exposure was associated with having talked to a health care provider about quitting smoking in the past 6 months and planning to quit smoking in the next 6 months. Conclusions Culturally specific outreach materials based on personal narratives are a promising population‐based intervention to motivate rural smokers to consider cessation.